Perceived safety management practices in the logistics sector - Auyong, H.N.; Zailani, S.; Surienty, L. (IOS Press, 2016)
BACKGROUND: Malaysia's progress on logistics has been slowed to keep pace with its growth in trade. The Government has been pressing companies to improve the safety of their activities in order to reduce society's loss due to occupational accidents and illnesses. Occupational safety and health is a crucial part of a workplace because every worker has to take care of his/her own safety and health. The main occupational safety and health (OSH) national policy in Malaysia is the enactment of the Occupational Safety and Health Act (OSHA) 1994. Only those companies which have excellent health and safety care have good quality and productive employees. This study investigated safety management practices in the logistics sector. OBJECTIVES: The present study is concerned with the human factors to safety in the logistics industry. The authors examined the perceived safety management practices of workers in the logistics sector. The purpose was to identify the perception of safety management practices of Malaysian logistics personnel. METHODS: Survey questionnaires were distributed to assess logistics personnel about management commitment. The quantitative method using the availability sampling method was applied. The data gathered from the survey were analysed using SPSS software. The responses to the survey were rated according to the Likert scale type, with '1' indicating strongly disagree and '5' indicating strongly agree. One hundred and three employees of logistics functions completed the survey. RESULTS: The highest mean scores were found for fire apparatus, prioritisation of safety, and safety policy. CONCLUSIONS: The results from this study also emphasise the importance of the management's commitment in enhancing workplace safety. Specifically, companies should maintain good relations between the employer and the employee to help reduce workplace injuries.